1999
DOI: 10.1159/000014102
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Enzymes Involved in Glutamine Metabolism in Connection with Energy Production in the Gastrointestinal Tract Epithelium of Newborn, Suckling and Weaned Piglets

Abstract: Changes in the activity of enzymes involved in glutaminolysis and energy metabolism in the entire gastrointestinal (GI) tract of developing piglets are presented for the first time. The activities of glutaminase, glutamate dehydrogenase, oxoglutarate dehydrogenase, isocitrate dehydrogenase and alanine aminotransferase in the epithelium along the gastrointestinal tract from newborn, suckling (2–4 weeks old) and weaned (9 weeks old) piglets were investigated. The activity of glutaminase in the epithelium from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
4
13
1
Order By: Relevance
“…The intestinal maturation is dependent on a rapid surge of corticosteroids during the weaning time, mainly via IGF-1 expression in the small bowel [33,34], modulating the intestinal adaptation to fit a new diet regimen of solid food, at the same time when glutamine and arginine metabolism is critical to enterocytes [35,36] in the small intestine is the highest during early development [37][38][39]. Among extrahepatic tissues, the adrenal gland has one of the highest concentrations of the apoE mRNA and the highest rate of apoE synthesis [40].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal maturation is dependent on a rapid surge of corticosteroids during the weaning time, mainly via IGF-1 expression in the small bowel [33,34], modulating the intestinal adaptation to fit a new diet regimen of solid food, at the same time when glutamine and arginine metabolism is critical to enterocytes [35,36] in the small intestine is the highest during early development [37][38][39]. Among extrahepatic tissues, the adrenal gland has one of the highest concentrations of the apoE mRNA and the highest rate of apoE synthesis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Even though avirulent strains of E. coli are a common constituent of intestinal microflora, pathogenic strains of the same bacteria are the most frequent causes of PWD in piglets (Madej et al, 1999;Madec et al, 2000;Melin et al, 2004). The acquiring of virulence factors happens by the enrichment of some E. coli strains through special mobile genes and with the joint influence of bacteriophages or plasmids.…”
Section: Intestinal Microflora In Pigletsmentioning
confidence: 99%
“…This inhibition effect is caused by competition for nutrients and binding sites, bacteriocin production, lactobacilli fermentations and short chain fatty acid production (Teitelbaum and Walker, 2002;Roselli et al, 2005). Subsequently, immunological memory is created and intestinal immunity develops (Jin et al, 1997;Makala et al, 2000;Stokes et al, 2004).Even though avirulent strains of E. coli are a common constituent of intestinal microflora, pathogenic strains of the same bacteria are the most frequent causes of PWD in piglets (Madej et al, 1999;Madec et al, 2000;Melin et al, 2004). The acquiring of virulence factors happens by the enrichment of some E. coli strains through special mobile genes and with the joint influence of bacteriophages or plasmids.…”
mentioning
confidence: 99%
“…In addition, epithelial cells in the pig intestine have notably high energy demands due to the rapid renewal of the epithelium (within few days) (2, 36). Previous studies showed the activities of key metabolic enzymes in enterocytes changed during the suckling-weaning transition in pigs (20,21). However, the effect of early weaning on the metabolism of enterocytes along the crypt-villus axis has not yet been elucidated.…”
mentioning
confidence: 99%